Biomechanical lower limb model to predict patellar position alteration after medial open wedge high tibial osteotomy. (May 2022) - Elyasi, Elaheh; Perrier, Antoine; Bailet, Mathieu; Payan, Yohan
Abstract: Medial open-wedge high tibial osteotomy is a surgical treatment for patients with a varus deformity and early-stage medial knee osteoarthritis. Observations suggest that this surgery can negatively affect the patellofemoral joint and change the patellofemoral kinematics. However, what causes these effects and how the correction angle can change the surgery's impact on the patellofemoral joint has not been investigated before. The objective of this study was to develop a biomechanical model that can predict the surgery's impact on the patellar position and find the correlation between the opening angles and the patellar position after the surgery. A combined finite element and multibody model of the lower limb was developed. The model's capabilities for predicting the patellofemoral kinematics were evaluated by performing a passive deep flexion simulation of the native knee and comparing the outcomes with magnetic resonance images of the study subject at various flexion angles. The model at a fixed knee flexion angle was then used to simulate the high tibial osteotomy surgery virtually. The results showed a correlation between the wedge opening angles and the patellar position in various degrees of freedom. These results indicate that larger wedge openings result in increased values of patellar distalization, lateral patellar shift, patellar rotation, and patellar internal tilt. The developed model in this study can be used in future studies to monitor the stress distribution on the patellar cartilage and connecting tissues to investigate their relationship with observations of pain and cartilage injury due to post-operative altered patellar kinematics.